Study of Photodegradation of Organic Solar Cells Under Brazilian Climate Conditions - Lucas Phillip Z. G. Moraes; Antonia Sonia A. C. Diniz; Marcelo Machado Viana; Lawrence L. Kazmerski; Gabriela A. Soares (Energies)
The increasing technical and economic viability of photovoltaic solar energy technologies includes modules with organic photovoltaic (OPV) cells, which have shown significant efficiency increases, reaching 20% for research devices. This study investigated the photodegradation and associated loss mechanisms in OPV devices under tropical conditions in Brazil. The electrical and optical characteristics of the modules were correlated with chemical and structural changes when exposed to sunlight. Electrical parameters were monitored over time on external test benches and measured in solar simulators, while changes in the optical transmission and absorption of the films were analyzed. Scanning electron microscopy, energy-dispersive spectroscopy, and Fourier-transform infrared spectroscopy were used to study the physical and chemical properties of the materials. We found that photodegradation causes bound breakage in the active layer, altering the carbon structure and consequently reducing the module’s output power. The primary reasons for the activation and progression of this mechanism are high temperature and elevated solar irradiance. Therefore, we demonstrate that understanding these mechanisms is essential for the development of more sustainable OPVs in tropical climates.